FUSD Board Candidate Jerry McMenamin and Friends Election Night at Mama Luz's - Watkins, Howard::::::::: (1989)
Computer screen with 222/226 precincts reporting: Curry 25.3%, Gadebusch 22.7% and McMenamin 19.2%, Leon 7.2% (top 3 (win)